Epoxide functionalization of a pentaethylenehexamine adsorbent supported on macroporous silica for post-combustion CO2 capture. (1st October 2022) - Ra Cho, A; Kim, Hana; Won, Yooseob; Lee, Yu-Ri; Kim, Jae-Young; Nam, Hyungseok; Jo, Sung-Ho; Cheol Park, Young; Lee, Dong-Ho
Graphical abstract: Highlights: The working capacity and stability of absorbent were studied for CO2 capture. MPS-supported epoxide-functionalization of PEHA absorbent was synthesized. PO-PEHA/MPS adsorbent exhibited the working capacity of 1.8 mmol g −1 in 20 cycle. When the adsorption time was reduced, the regeneration heat was 2.86 GJ tCO2 -1 . Adsorbent that is regenerated in 100% CO2, not inert (N2, He) conditions was developed. Abstract: N -functionalized solid adsorbents have been studied for post-combustion CO2 capture. Most studies have focused only on the adsorption condition of the adsorbents. Few studies have focused on the regeneration condition of adsorbents. Regeneration is required under the condition of 100 % CO2 for high-purity CO2 separation. Regeneration under inert conditions such as N2 or He, not under the condition of 100 % CO2 regeneration are required additional cost for high-purity CO2 separation. In this study, a macroporous silica (MPS) support, which combined a high surface area, large porosity and large pore volume, was selected as the support to achieve high CO2 capture performance. Pentaethylenehexamine (PEHA) was selected because of its high amine content, high adsorption capacity, high thermal stability, and low cost. The epoxide functionalization of PEHA was used to suppress the urea formation under regeneration conditions. The working capacity and cyclic stability of epoxide functionalization of MPS-based PEHA adsorbents were investigated. A working capacity of 1.8 mmol g −1 was maintained by repeating adsorption and desorption experiments 20 times under an adsorption condition of 15 % CO2 and a desorption condition of 100 % CO2 . Additionally, the stability of the adsorbent under a 100 % CO2 regeneration condition was confirmed by maintaining the working capacity constant during 20 repeated adsorption and desorption cycle experiments. When the adsorption time was reduced to minimize H2 O adsorption, the regeneration heat of the adsorbent was 2.86 GJ tCO2 -1 . These results demonstrated that the regeneration ability was excellent under the condition of 100 % CO2, which is the actual process application condition. This approach is promising for industrial applications of CO2 capture technology.